Penguatan Literasi Digital melalui Pelatihan EDU-MAD bagi Guru dan Tenaga Kependidikan di MTS dan MA Salafiyah Kerek Tuban - Albaar, Ragwan; Amriana, Amriana (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This community service activity aims to improve digital literacy among teachers and education staff at MTs and MA Salafiyah Kerek Tuban, who face challenges in online learning due to the COVID-19 pandemic. The main problem identified is the low quality of online learning, characterized by minimal student interaction, teachers’ difficulty adapting to technology, and a decline in students' learning interest. To address this, the implementation utilized the Participatory Action Research (PAR) method, actively involving partners in planning, executing, and evaluating the program. Activities included training on digital literacy concepts, creating digital learning media, practicing the use of digital tools, preparing modules, and disseminating program results. The outcomes of this community service indicated significant improvements in two aspects: behavior and learning patterns. Behavioral changes were marked by an increase in students' interest in online learning, while changes in learning patterns were evidenced by teachers’ adoption of digital media, such as interactive presentations and videos, replacing conventional methods that relied solely on textbooks and homework. In conclusion, this training successfully enhanced digital literacy and the effectiveness of online learning at MTs and MA Salafiyah Kerek Tuban.